2017
DOI: 10.3732/ajb.1600301
|View full text |Cite
|
Sign up to set email alerts
|

A wild origin of the loss‐of‐function lycopene beta cyclase (CYC‐b) allele in cultivated, red‐fleshed papaya (Carica papaya)

Abstract: PREMISE OF THE STUDY:The red fl esh of some papaya cultivars is caused by a recessive loss-of-function mutation in the coding region of the chromoplastspecifi c lycopene beta cyclase gene ( CYC-b ). We performed an evolutionary genetic analysis of the CYC-b locus in wild and cultivated papaya to uncover the origin of this loss-of-function allele in cultivated papaya. METHODS:We analyzed the levels and patterns of genetic diversity at the CYC-b locus and six loci in a 100-kb region fl anking CYC-b and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…By means of a haplotype network, the authors suggest that the y allele likely originated in the wild and was introduced into the domesticated varieties during the domestication of papaya. However, they found shared haplotype structure among some wild, feral, and cultivated haplotypes near the y allele, suggesting a successive escape of the y allele from red cultivars back into wild populations, probably through feral intermediates in Costa Rica (Wu et al, 2017). In other study, Porter et al (2009), using a genome-wide analysis, revealed that papaya has relatively few nucleotide-bindings sites (NBS) encoding genes, but structurally diverse showing a novel subgroup.…”
Section: Genetics and Genomicsmentioning
confidence: 97%
See 1 more Smart Citation
“…By means of a haplotype network, the authors suggest that the y allele likely originated in the wild and was introduced into the domesticated varieties during the domestication of papaya. However, they found shared haplotype structure among some wild, feral, and cultivated haplotypes near the y allele, suggesting a successive escape of the y allele from red cultivars back into wild populations, probably through feral intermediates in Costa Rica (Wu et al, 2017). In other study, Porter et al (2009), using a genome-wide analysis, revealed that papaya has relatively few nucleotide-bindings sites (NBS) encoding genes, but structurally diverse showing a novel subgroup.…”
Section: Genetics and Genomicsmentioning
confidence: 97%
“…For instance, Wu et al (2017) found evidence of a recent emergence of the y allele and its selection in red fruited cultivation. Analysing the levels and patterns of genetic diversity at the CYC-b locus (y allele) and six loci in a 100-kb region flanking this locus, they found evidence of a strong selective sweep, as genetic diversity showed a reduction at the recessive y allele in comparison with the dominant Y allele present in the yellow-fleshed papayas (wild and cultivated).…”
Section: Genetics and Genomicsmentioning
confidence: 99%
“…To date, dozens of enzymes have been identified with a function in carotenoid biosynthesis and metabolism (Nisar et al, 2015;Hermanns et al, 2020). For fruit production crops, natural variations in IPI (Isopentenyl diphosphate isomerase), PSY (phytoene synthase), CRTISO (carotenoid isomerase), LCYB (lycopene b-cyclase), ZEP (zeaxanthin epoxidase), OR (Orange), and NCED/CCD (9-cisepoxycarotenoid dioxygenase/carotenoid cleavage dioxygenase) genes resulted in diverse colored fruits ranging from white, yellow, pink, orange to red in tomato (Pankratov et al, 2016;Yoo et al, 2023), pepper (Lee et al, 2021), watermelon (Bang et al, 2007;Liu et al, 2021), melon (Tzuri et al, 2015), citrus (Zheng et al, 2019), peach (Falchi et al, 2013), papaya (Wu et al, 2017) and loquat (Fu et al, 2014). These genes encode enzymes that function in the carotenoid biosynthesis and metabolism pathway.…”
Section: Introductionmentioning
confidence: 99%